MENINGKATKAN KUALITAS PRODUK SEBAGAI STRATEGI FUNDAMENTAL DALAM BERSAING - Roidah Lina (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
For manufacturing companies, especially in the food and beverage sector presenting the quality of products is the principle, therefore consumers buying products. Therefore, this research was conducted. The aim is to analyze the effect of product quality on satisfaction and consumer loyalty. To study this research a quantitative approach was used, and the object of research is one food and beverage company, PT. Kobe Boga Utama. The sample technique used is Accidental Sampling amounting 97 respondents. The analytical method used is linear regression consisting of validity, reliability, correlation coefficient, determination coefficient, regression tests, and hypothesis testing. The results show that product quality is the reason consumers loyal. In the quality of products there is a value of customer satisfaction, in this case is the taste